The role of Six1 in the genesis of muscle cell and skeletal muscle development - Wu, Wangjun; Huang, Ruihua; Wu, Qinghua; Li, Pinghua; Chen, Jie; Li, Bojiang; Liu, Honglin (International journal of biological sciences, 2014)
The sine oculis homeobox 1 (Six1) gene encodes an evolutionarily conserved transcription factor. In the past two decades, much research has indicated that Six1 is a powerful regulator participating in skeletal muscle development. In this review, we summarized the discovery and structural characteristics of Six1 gene, and discussed the functional roles and molecular mechanisms of Six1 in myogenesis and in the formation of skeletal muscle fibers. Finally, we proposed areas of future interest for understanding Six1 gene function.
Keywords: homeodoménové proteiny; buněčný rodokmen; kosterní svaly; druhová specificita; Animals; regulace genové exprese; Gene Expression Regulation; Cell Lineage; Homeodomain Proteins; zvířata; Muscle, Skeletal; Species Specificity